Clinical impact of MDR1-expression in testicular germ cell cancer - Schrader, A.J.; Seger, M.; Konrad, L.; Olbert, P.; Hegele, A.; Hofmann, R.; Heidenreich, A. (Experimental Oncology, 2007)
Aim: The multidrug resistance protein 1 (MDR1, P-gp, p-170) is a membrane glycoprotein that acts as an energy-dependent drug efflux pump. In various malignancies its expression is associated with resistance to diverse cytostatic drugs, and therefore predicts resistance to systemic treatment. The aim of this study was to investigate the prognostic value of MDR1 expression in primary tumor tissue to predict necrosis or viable cancer in residual tumor masses after systemic chemotherapy for advanced testicular germ cell cancer. Materials and Methods: Out of 77 patients, histopathological characteristics of primary testicular cancer specimens and retroperitoneal lymph node dissection (RPLND) samples following chemotherapy were available from 72 and all 77 patients, respectively. Moreover, MDR1 expression was determined by immunohistochemistry in 47 primary tumors and corresponding 73 RPLND sections. Results: After chemotherapy and subsequent RPLND, the examination of residual tumor masses revealed that mature teratoma and active viable tumor were predominantly found in patients with non-seminoma (NSGCT; p = 0.048), especially in those with containing mature teratoma (p = 0.001). Moreover, using univariate analysis the expression of MDR1 in the primary testicular tumor predicted viable tumor/teratoma residues in RPLND sections (p = 0.003). However, in multivariate analysis including the tumors’ histological subtype, MDR1 expression alone failed to reach statistical significance as an independent prognostic marker for residual vital tumor (p ≥ 0.16). Conclusions: With the limited number of patients given, the correlation between MDR1 expression in primary testis cancer and active residual retroperitoneal disease after chemotherapy failed to reach statistical significance as in independent marker. Therefore, up to now routine MDR1 staining of testicular germ cell cancer samples should not be performed in clinical practice. However, as there was a clear trend, a larger number of patients suffering from metastatic non-seminomas should be studied, as MDR1 expression might have significant prognostic value in this particular subgroup of patients. Белок 1 множественной лекарств енной устойчив ости (MDR1, P-gp, p-170) – это мембранный гликопротеин, функционирующий как энергозависимый насос. При разл ичных фо рмах опухолей его экспр е ссия связана с устойчив о стью опухоли к различным цитостатикам, что может быть использовано для выбора типа терапии. Цель работы — исследование прогности- ческой значимости экспрессии MDR1 в ткани пе рвичной опухоли для оценки возмо жности раз вития некроза или сохран е ния живых клеток в остаточной ткани опухоли после применения системной химиотерапии на поздних стадиях герминативных опухолей яичка. Материалы и методы: про анализиро ваны гисто патоло гические характ е ристики пе рвично й те стикулярной опухоли и образцов, полученных при иссечении ретроперитонеальных лимфатических узлов (RPLND) после хими отерапии 72 и 77 бол ьных соотве тственно. Экспр ессию MDR1 определяли иммун огист охимич еским методом в 47 образцах первичн ой опухоли и соответствующих 73 ср RPLND. Результаты: после хими отерапии и последующей RPLNDисследовани е оста- точных опухолевых тканей показало, чтозрелая тератома и жизнеспособные опух олевые клетки выяв ляют преимущественно у больных, у которых не была обнаружена семинома (NSGCT; p = 0,048), особенно у так овых , у которых была тератома (p = 0,001). Более того, д анные одно факторного анализа показали, что экспр е ссия MDR1 в ткани пе рвично й те стику лярной опу- холи может служить прогностич еским факт ором сохран ения живых опух олевых клеток срезах RPLND (p = 0,003). О нак о применение мультифакторного анализа, в том числе с учетом гистологического подтипа опухоли, показало, что экспр е ссия MDR1 не имеет самостоятельной прогностической значимости для выявления живых остаточных опух олевых клеток (p 0,16). Выводы: ввиду небольшо йвыборкибольных не выяв лено статистически значимойкорреляции между экспр ессией MDR1 в первичной опухоли яичка и наличием активных резидуальных очагов поражения в ретроперитонеальном пространстве. В т о же время, учитывая выявленную тенденцию, экспрессию MDR1, в качестве возможного прогностич еского марк ера, имеет смысл исследовать именно у больных с метастатическими опухолями, не являющимися семиномой.